Casey-Fink Graduate Experience Survey for Nurses and Preceptors in the Kingdom of Saudi Arabia - Baker, Omar Ghazi; Alghamdi, Musaad Salem (Department of Nursing, Faculty of Medicine, Diponegoro University, 2020)
Background: Preceptors play an essential role in supporting new nurses during the transitional period in professional roles. Moreover, graduate nurses experience several challenges during their transitional role from students to professional nurses, despite the considerable relationship between nurses and preceptors.Purpose: The study aims to evaluate the relationship between the experiences of nurses using Casey-Fink Graduate Nurse Experience Survey and the number of preceptors in Saudi hospitals.Methods: A cross-sectional study design was adopted, and Casey-Fink Graduate Nurse Experience Survey was used to collect data from 84 newly graduated nurses. Descriptive and regression analysis was used for data analysis.Results: Results showed that there was no statistically significant relationship between the responses of 5 factors of the Casey-Fink Graduate experience survey and the number of preceptors. Based on the survey, (33.8%) had to stress whereas significant causes of stress were student loans (41.9%), personal relationships (13.5%), living situation (27%), and finances (10.8%).Conclusion: No statistically significant relationship was found between variables including; support, patient safety, communication/leadership, professional satisfaction, and job satisfaction. The significance of preceptorship programs should be considered by the primary health care corporation to support and prepare preceptors of newly graduated and recruited nurses.